The decreased connectivity in middle temporal gyrus can be used as a potential neuroimaging biomarker for left temporal lobe epilepsy - Wu, Jinlong; Wu, Jun; Guo, Ruimin; Chu, Linkang; Li, Jun; Zhang, Sheng; Ren, Hongwei (Frontiers in Psychiatry, 2022)
Objective: While prior reports have indicated that left temporal lobe epilepsy (lTLE) is associated with distinct neuroimaging features, the potential diagnostic utility of lTLE-related voxel-mirrored homotopic connectivity (VMHC) alterations has yet to be assessed. Accordingly, the present study was developed to explore VMHC abnormalities between the two brain hemispheres in lTLE patients and to determine whether these alterations could be leveraged to guide lTLE diagnosis. Methods: In total, this study enrolled 58 lTLE patients and 60 age-, sex-, and education level-matched healthy control (HC) individuals. Resting-state functional magnetic resonance imaging (rs-fMRI) was used to evaluate all study participants, with VHMC analyses of bilateral brain regions then being conducted based on the results of these rs-fMRI scans. The resultant imaging data were further analyzed using support vector machine (SVM) methods. Results: As compared to HCs, patients with lTLE exhibited decreased VMHC values in the bilateral middle temporal gyrus (MTG) and middle cingulum gyrus (MCG), while no brain regions in these patients exhibited increased VMHC values. SVM analyses revealed the diagnostic accuracy of reduced bilateral MTG VMHC values to be 75.42% (89/118) when differentiating between lTLE patients and HCs, with respective sensitivity and specificity values of 74.14% (43/58) and 76.67% (46/60). Conclusion: The results of this study suggested that lTLE patients exhibit abnormal VMHC values corresponding to the impairment of functional coordination between homotopic regions of the brain. Adversely affected MCG and MTG function may represent a critical node linked to cognitive dysfunction in lTLE patients. These altered MTG VMHC values may also offer value as a robust neuroimaging biomarker that can guide lTLE patient diagnosis.